Glosa do postanowienia Sądu Najwyższego z dnia 23 marca 2016 r., sygn. akt: III CZP 112/15 - Kozioł, Agata (Problemy Prawa Prywatnego Międzynarodowego, 2020)
The role of art. 57 § 1 of Polish Family and Guardianship Code in proceedings concerning international divorce is disputed and gives rise to many questions concerning its nature. The provision, addressed to the Polish courts dealing with divorce cases, obliges the seized court to rule on fault of spouses in the breakdown of marriage. It may then seem to remain unclear if the court shall apply art. 57 § 1 when the law applicable to divorce does not state for fault based grounds for dissolution of marriage, while the legal order applicable to maintenance obligation between former spouses requires, among other prerequisites, that the fault of the former spouse obliged to alimony is declared in court proceedings. This paper analyses the judgement of Polish Supreme Court from 23rd of March 2016, in which this issue was raised. The Author rejects the opinion of Supreme Court that the provision in question has a procedural nature. The view, that it constitutes an example of overriding mandatory provision should also be denied. As a provision of double nature: material and procedural, it should be applied by Polish courts as an instrument that enables to rule on fault in all those cases when applicable law provides for fault grounds for divorce; it should be also applied by foreign court deciding on dissolution of marriage when Polish law is applicable.